Failure patterns and outcomes of dose escalation of stereotactic body radiotherapy for locally advanced pancreatic cancer: a multicenter cohort study. (December 2020) - Zhu, Xiaofei; Cao, Yangsen; Su, Tingshi; Zhu, Xixu; Ju, Xiaoping; Zhao, Xianzhi; Jiang, Lingong; Ye, Yusheng; Cao, Fei; Qing, Shuiwang; Zhang, Huojun
Objective: This study aims to compare recurrence patterns and outcomes of biologically effective dose (BED10, α/β = 10) of 60–70 Gy with those of a BED10 >70 Gy for locally advanced pancreatic cancer (LAPC). Methods: Patients from three centers with a biopsy and a radiographically proven LAPC were retrospectively included and data were prospectively collected from June 2012 to June 2019. Radiotherapy was delivered by stereotactic body radiation therapy. Recurrences were categorized as in-field, marginal, and outside-the-field recurrence. Patients in two groups were required to receive abdominal enhanced contrast CT or MRI every 2–3 months and CA19-9 examinations every month during follow-up. Treatment-related toxicities were evaluated every month. Overall survival (OS) and progression-free survival (PFS) were estimated using the Kaplan–Meier method. Results: After propensity score matching, there were 486 patients in each group. The median prescription dose of the two groups was 37 Gy/5–8 f (range: 36–40.8 Gy/5–8 f) and 42 Gy/5–8 f (range: 40–49.6 Gy/5–8 f), respectively. The median OS of patients with a BED10 >70 Gy and a BED10 60–70 Gy was 20.3 months (95% CI: 19.1–21.5 months) and 18.2 months (95% CI: 17.8–18.6 months) respectively ( p < 0.001). The median PFS of the two cohorts was 15.4 months (95% CI: 14.2–16.6 months) and 13.3 months (95% CI: 12.9–13.7 months) respectively ( p < 0.001). A higher incidence of in-field and marginal recurrence was found in patients with BED10 of 60–70 Gy (in-field: 97/486 versus 72/486, p = 0.034; marginal: 109/486 versus 84/486, p = 0.044). However, more patients with BED10 >70 Gy had grade 2 or 3 acute (87/486 versus 64/486, p = 0.042) and late gastrointestinal toxicities (77/486 versus 55/486, p = 0.039) than those with BED10 of 60–70 Gy. Conclusion: BED10 >70 Gy was found to have the best survival benefits along with a higher incidence of acute and late gastrointestinal toxicities. Therefore, a higher dose may be required in the case of patients' good tolerance.